Detrital zircon analysis of the southwest Indochina terrane, central Thailand: Unravelling the Indosinian orogeny - Francesco Arboit (2018)
© 2016 Geological Society of America. The Khao Khwang fold-and-thrust belt, central Thailand, developed within a basin that formed on the southwestern margin of the Indochina block. Because of limited geochronological and provenance constraints, the time of deposition, sediment source location, and tectonic significance of the basin have been uncertain. Here, we present 837 U-Pb detrital zircon ages and 271 Hf isotope in situ analyses from Permian-Triassic clastic units within the Khao Khwang fold-andthrust belt in order to constrain the provenance, maximum depositional ages, and depositional environment of the southwestern margin of the Indochina terrane through the late Paleozoic to early Mesozoic. The key lithological units, the Sap Bon, Pang Asok, and Nong Pong Formations, are part of the Saraburi Group and have detrital age spectra spanning from Late T3 Triassic to Paleoarchean. The entire data set has a common age peak at ca. 450 Ma, and all samples contain grains with ages of 0.2-0.3, 0.4-0.6, 1.0-1.3, 1.7-1.8, and 2.2-2.7 Ga. A few grains predate 3.0 Ga. Multidimensional scaling analysis of detrital zircon ages from throughout SE Asia demonstrates that the age spectra of the siliciclastic units of the Saraburi Group resemble those of Permian-Triassic detritus found elsewhere in the Khorat Plateau and throughout Vietnam and southeast China, implying that these areas shared similar sources. These sources may have been the, now largely covered, Indochina basement, and/or contiguous continental crust in terranes already amalgamated to Indochina at that time. Detrital zircons as young as 205 ± 6 Ma show that some formations of the Saraburi Group, previously considered to be of Middle-Late Permian age, are no older than Late Triassic. We propose a depositional model for the region of a Permian rift or passive-margin setting that evolved into piggyback and foredeep basins during an extended period of folding and thrusting in the Triassic.